Environmental Shocks and Sustainability in Microfinance : Evidence from the Great Famine of Ireland - Goodspeed, Tyler Beck (Published by Oxford University Press on behalf of the World Bank, 2019)
I study the effects of a major environmental shock on microfinance lending by analyzing the Irish Loan Funds during the Great Famine of Ireland. I find that funds in districts worse affected by blight experienced higher failure rates and greater credit retrenchment and flight-to-quality than funds in less affected districts. Though greater leverage was generally associated with a higher predicted probability of institutional survival, the reverse was true where blight infection was more severe, and though more profitable funds were generally no more likely to survive, higher pre-famine margins were positive predictors of institutional survival where blight infection was worse. Results further indicate that the primary mechanisms by which pre-famine balance sheet metrics influenced survival probabilities were differential balance sheet contraction and flight-to-quality during the famine. The results of this study, therefore, suggest that optimal lending models in ordinary circumstances may render microfinance institutions (MFIs) more vulnerable to tail-probability aggregate shocks, with higher leverage, lower paid staff, lower economic rents, and more extensive liabilities limiting the scope for credit retrenchment and flight-to-quality. Results further indicate that one cost of MFI resilience to adverse environmental change is substantially reduced outreach to borrowers of lower credit quality.